The Urgency of Multicultural Islamic Education in Developing Tolerance and National Character - Aisyh Anggun Putri; Najmi Nur Affifah; Titin Sumarni; Lutfiana Sukmaningrum; Asniti Karni; Dayun Riadi (Journal of Social Work and Science Education, 2026)
This study aims to describe the urgency of multicultural Islamic education in building national tolerance and character. Using a literature-based research method, this study analyzes various documents, books, and previous research results to provide a theoretical foundation for the issues being researched: First, the urgency of multicultural Islamic education in promoting tolerance and instilling a moderate religious understanding (wasathiyyah) lies in its function as a tool for social and spiritual change. Through a multicultural approach, students are encouraged to understand Islamic teachings contextually, appreciate diversity, and reject all forms of extremism. This moderate religious understanding lays a strong foundation for a harmonious, just, and cultured society. Second, Islamic education with a multicultural approach plays a crucial role in strengthening the character of the diverse Indonesian nation. By respecting differences, this education instills global values of harmony, justice, and humanity. It not only strengthens students’ Islamic identity but also shapes a national character grounded in solidarity and unity. Therefore, multicultural Islamic education serves as the main foundation for realizing an Indonesian society that is religious, moderate, and possesses a strong national character.